Integration of organic and inorganic amendments with native bioagents for bio-intensive management of vascular bacterial wilt on eggplant (Solanum melongena) - and A. CHATTOPADHY, P.P. GHOSH, S. DUTTA* (Indian Phytopathology, 2015)
The potential of biocontrol consortium and organic/inorganic soil amendments as the major component of biointensive management strategy of Ralstonia solanacearum induced vascular bacterial wilt on eggplant (Solanum melongena L.) in New Alluvial region of West Bengal was studied. The in vitro antagonistic potential of native rhizospheric fluorescent pseudomonads (PF) revealed that PF-3, followed by PF-2 produced highest inhibition zone 5.19 mm and 4.26 mm, respectively. Further, only PF-2 was able to inhibit all the R. solanacearum isolates. Among different organic amendments tested, green manuring with dhaincha leaf (25 q/ha)and application of neem cake (500 kg/ha) one month before transplanting were the most effective treatments in terms of disease reduction by 42.3% and 41.57%, respectively, over the control. Among different inorganic amendments, application of bleaching powder (20 kg/ha) followed by lime (500 kg/ha), one month before transplanting, were most effective treatments in terms of disease reduction up to 44.91% and 28.04%, respectively over the control. The integration module constituting green manuring with dhaincha leaf (25 q/ha) + bleaching (20 kg/ha) + lime (500 kg/ha) + consortium of fluorescent pseudomonads (PF-2 and PF-3) (seedling treatment and soil spot application) was the best performer among seven different modules, both in terms of disease reduction (72.25%), enhancing yield (11.8 t/ha) over the control. The present investigation indicated that exploitation of biodiversity with organic and inorganic amendment towards assistance for preferential adaptation of native biological consortia is indeed able to suppress this versatile complex pathogen.